Norway : Financial Sector Assessment Program-Technical Note-Insurance Sector Stress Tests. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note presents key findings of insurance sector stress tests on Norway. Although the financial condition of insurance companies under Solvency I has generally been sound, insurers face major challenges going forward, thus placing an important premium on sound risk management and effective oversight by supervisors. The stress tests (under Solvency II) confirm that life insurers are vulnerable to severe shocks. The stress tests pointed to the high sensitivity of life insurers to market risks such as equity prices, real estate prices, and credit spreads. The risks to insurers are particularly pronounced if interest rates fall further from the current levels.